2021
DOI: 10.24912/psenapenmas.v0i0.15157
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Influencer Marketing Dan Viral Marketing Terhadap Keputusan Pembelian Bittersweet by Najla

Abstract: Bittersweet By Najla is known as a marketer who uses influencer marketing and viral marketing methods. Although this method is known as a powerful marketing method, sales of new products marketed using influencer marketing and viral marketing are not in line with the old products that people are familiar with. This study aims to prove the influence of influencer marketing on purchasing decisions and viral marketing on purchasing decisions. This research is a descriptive quantitative study with the object of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Several previous studies by (Sari & Hidayat, 2021); (Lengkawati & Saputra, 2021); dan (Fathurrahman et al, 2021), have concluded that influencer marketing has a positive and significant influence on purchase decisions. Individuals are more likely to make a purchase decision when they see a high number of followers or subscribers of an influencer.…”
Section: The Relationship Between Influencer Marketing and Purchase D...mentioning
confidence: 95%
“…Several previous studies by (Sari & Hidayat, 2021); (Lengkawati & Saputra, 2021); dan (Fathurrahman et al, 2021), have concluded that influencer marketing has a positive and significant influence on purchase decisions. Individuals are more likely to make a purchase decision when they see a high number of followers or subscribers of an influencer.…”
Section: The Relationship Between Influencer Marketing and Purchase D...mentioning
confidence: 95%
“…Customers in this era often use viral social media content to make purchasing decisions. Tendean & Mananeke (2020), Septhi & Hidayat (2021), and Fathurrahman et al (2021) show that viral marketing has a positive and significant impact on purchase decisions. H1: Viral marketing on Instagram has a positive effect on purchasing decisions for Mixue ice cream in Surabaya.…”
Section: Relationship Between Variablesmentioning
confidence: 99%
“…Influencer marketing berpengaruh positif pada keputusan pembelian, karena didukung dari hasil penelitian (Fathurrahman et al, 2021) yaitu variabel influencer marketing berpengaruh positif serta signifikan pada keputusan pembelian. Dengan kesimpulan penggunaaan influencer untuk mempromosikan produk mempengaruhi seseorang untuk dapat melakukan pembelian produk dari bittersweet by najla H1 : Influencer marketing berpengaruh terhadap keputusan pembelian produk Scarlett Whitening pada mahasiswa FEB UNESA.…”
Section: Pendahuluanunclassified